A Pilot Randomized Controlled Trial of a Technology-Based Approach for Preventing Excess Weight Gain during Pregnancy among Women with Overweight - Chao, Ariana M.; Srinivas, Sindhu K.; Studt, Stacia K.; Diewald, Lisa K.; Sarwer, David B.; Allison, Kelly C. (Frontiers in Nutrition, 2017)
Objective: Overweight/obesity and excess weight gain during pregnancy are associated with adverse maternal and neonatal outcomes. Few interventions have been effective in limiting gestational weight gain among women with overweight or obesity. This pilot, randomized clinical trial compared treatment as usual (TAU) to a lifestyle modification program delivered via phone for the prevention of excess gestational weight gain in women who had overweight or obesity. Methods: Participants included 41 pregnant women with a BMI >/= 25 kg/m2 (mean age=28.7+5.8 years; mean pre-gravid BMI=31.2+6.2 kg/m2; 54% black, 39% white). The intervention group (n = 20) received weekly telephone counseling sessions and used WiFi scales to monitor their weight from weeks 16 to 36 of pregnancy. We compared differences in weight and birth outcomes for the intervention versus the TAU group (n = 21). Results: The intervention and TAU groups did not differ with respect to: gestational weight gain (15.5+5.3 kg vs. 13.3+6.8 kg, respectively); proportion gaining above the 2009 IOM recommended weight range (83% vs. 70%); and weight gain from pre-pregnancy weight to 6 weeks postpartum (4.8+4.6 kg vs. 3.0+5.5 kg). Other birth and health outcomes also did not differ. Conclusions: A telemedicine intervention designed to decrease logistical burden on participants was not more successful in reducing excessive weight gain during pregnancy as compared to TAU. Future studies should examine more intensive forms of remote treatment beginning earlier in pregnancy as well as interventions promoting a healthy weight prior to pregnancy.